Menilik Problematika Dispensasi Nikah Dalam Upaya Pencegahan Pernikahan Anak Pasca Revisi UU Perkawinan - Ahmad Muqaffi; Rusdiyah Rusdiyah; Diana Rahmi (Fakultas Syariah UIN Antasari, 2021)
Abstract: Highlighting the potential discrepancy between the Child Protection Law (No. 35/2014) and the Marriage Law (No. 16/2019) in the issue of marrying children under the minimum age of marriage, which is 19 years. Parents are obliged to